The temporal change of heat exposure and adaptation capacity in Chinese adults from 1994 to 2023 - Xiaohui Ji; Haomin Tan; Shaoli Huang; Zhongguo Huang; Jianxiong Hu; Jianxiong Hu; Guanhao He; Fengrui Jing; Ziqiang Lin; Mengen Guo; Tao Liu; Wenjun Ma; et al. (Frontiers in Public Health)
BackgroundStudies have found decreased heat effect and increased minimum mortality temperature (MMT) during the past decades. However, it is unclear whether heat exposure or temperature adaptation play an important role in this change.MethodsThis is a cross-sectional study. Data were collected from 3,094 respondents aged 31–64 years old based on online questionnaire. The Cochran-Armitage test for trend and Cochran–Mantel–Haenszel (CMH) test were used for the difference between three decades. The Chi square test was employed to compare the difference between different demographic subgroups during 2014–2023. Multivariate logistic regression model was used to analyze the risk factors of air conditioner ownership.ResultsMost respondents (94.6%) thought ambient temperature had been increasing, and 57.0% people thought climate change impacted their health. Long duration outdoors work (≥4 h) decreased from 36.01, 30.93 to 24.53% (Z = −9.80, p < 0.01) and bicycling/walking decreased from 62.3, 27.9, to 9.7% (CMH value = 156.40, p < 0.01) significantly during the last three decades. Temperature adaptation capacity increased with air conditioner ownership rates increasing from 25.40, 57.63 to 81.51% at home (Z = −44.35, p < 0.01) and from 22.24, 57.47 to 80.51% in the office/school (Z = −45.95, p < 0.01), and the older adult, women, people with low income, outdoor work, low education, and people from northern China had lower air conditioner ownership rates. The frequency of air conditioner usage when felt hot also escalated significantly both at home (from 42.6%, 54.9, to 63.4%, CMH value = 156.40, p < 0.0001) and in the office/school (from 61.8, 63.1 to 72.7%, CMH value = 65.29, p < 0.0001) during the same periods.ConclusionOur study found that most people perceived climate change and changed behaviors to adapt to heat. Heat exposure significantly decreased and temperature adaptation capacity significantly increased during the last decades. The findings implied that heat-related health risk and burden driven by global warming may not increase in the future.